O imaginário e a identidade política regional construídos pela imprensa mineira no século XIX - Márcio Achtschin Santos (2013)
Trying to analyze the representations constructed by the elite mining through provincial press throughout the empire, this work seeks to interpret especially the political imaginary, regional identity and the myths constructed by this group. Within a logic of its own, albeit often contradictory and full of feelings experienced and translated into various representations , the purpose of this research is to reconstruct a portion of that reality into what documentation can offer. Using the new trends for the analysis of political history, from the contributions related to social science concepts, this thesis aims to understand the relationship of mining elites and their joints with power in the nineteenth century, whether in the arena or outside the State . Thus, including representations as symbols, myths and beliefs, aims to understand the various ways that miners identified themselves within relationships imperial policies.